Brain Metastases: Outcome related to prognostic indices: Critical Review in a Single institutional Experience - Gill, Maneet; Carlvalho, Ajaya Sebastian; Srivastava, Chinmaya; Agarwal, Sudhanshu; Gupta, Vijaya Kumar; Sudharshana, Kola (Nepal Journal of Neuroscience, 2023)
Introduction: Brain metastases are the most common brain tumour. There are various prognostic indicators which determine the overall outcome and survival of the patient. To study the outcome of the patients of cerebral metastases based on various indices and to correlate the prognostic significance of these indices. Material and Methods: A total of 123 surgically resected cases of brain metastases from July 2007 to July 2017 were included in the study. The clinical details including the age, gender, clinical features, location of the primary, status of control of primary disease, Karnofsky performance status, number and intracranial location of the metastases were obtained. The follow up period for the study was at least 36 months. Results: The prognostic factors associated with better survival were KPS > 60 (p value < 0.0001), controlled status of the primary malignancy (p value < 0.0001), age < 50 yrs (p value< 0.0001) and number (<3) of metastases (p value < 0.000). Gender (p value = 0.902), primary site (P = 0.758) and location of intracranial metastases (P = 0.575) had no significant impact on the survival. Conclusion: Of the various prognostic indices, patients with KPS > 60, well controlled primary malignancy, age <50 yrs. and number of metastases less than 3, were related to statistically significant better prognosis and survival.